The value of the reflective discussion in decision-making using multi-criteria decision analysis (MCDA): an example of determining the value contribution of tabelecleucel for the treatment of the Epstein Barr virus-positive post-transplant lymphoproliferative disease (EBV+ PTLD) - Xavier Badia; Miguel Ángel Calleja; Vicente Escudero-Vilaplana; Antonio Pérez-Martínez; José Luis Piñana; José Luis Poveda; Joan-Antoni Vallès (Orphanet Journal of Rare Diseases, 2024)
Abstract Background The aim of this study was to assess the contribution of the reflective multidisciplinary discussion in determining the value contribution of innovative drugs through the multi-criteria decision analysis (MCDA). This methodology considers all relevant criteria for healthcare decision-making in a global, transparent, and systematic manner and from the perspective of relevant stakeholders. The determination of value contribution of tabelecleucel for the treatment of Epstein-Barr virus-positive post-transplant lymphoproliferative disease (EBV+ PTLD) compared to salvage therapy was used as an example. Results Tabelecleucel obtained a value contribution score of 0.63 and increased to 0.75 after the reflective discussion. EBV+ PTLD was considered a life-threatening disease (5.0 ± 0.0), with a significant unmet need for an approved treatment (5.0 ± 0.0). Tabelecleucel was perceived as bringing improvements in terms of efficacy (4.2 ± 0.8) and safety (3.8 ± 0.8) compared to the salvage therapy. Most experts considered that the high efficacy and safety results could represent an improvement in the quality of life of patients (2.3 ± 1.2) along with savings in medical costs (2.3 ± 2.0) and non-medical costs (2.7 ± 1.6) compared to the salvage therapy. However, others emphasized the need of more evidence to confirm these improvements and savings over time. Tabelecleucel was regarded as potentially modifying the clinical course of the disease (4.3 ± 0.8) and supported by high-quality evidence (3.2 ± 0.4). All contextual criteria were valued highly positively for tabelecleucel. "Safety/Tolerability" and "Other medical costs" were the criteria that experienced the highest change in the re-test conducted after the reflective discussion. The reflective discussion allowed resolving doubts or misinterpretations of the experts, so the re-test obtained more accurate and consistent results of the value contribution of tabelecleucel. Conclusions The study shows that the MCDA methodology is a useful tool for decision-making on innovative treatments for the management of rare diseases. It also highlights the importance of reflective multidisciplinary discussion for its ability to resolve doubts or misinterpretations of experts, subsequently allowing to obtain more consistent and reliable results on the value contribution of the drug, being potentially more positive.